Microstructural and textural evolution of commercially pure Zr sheet rolled at room and liquid nitrogen temperatures. (15th November 2015) - Chai, Linjiang; Luan, Baifeng; Xiao, Dongping; Zhang, Min; Murty, Korukonda L.; Liu, Qing
Abstract: A commercially pure Zr sheet with a typical bimodal basal texture was rolled up to 70% reductions at room temperature (RT) and liquid nitrogen temperature (LNT) to follow its microstructural and textural evolution. Various features developed during rolling were interpreted largely based on analyses on active deformation modes by the use of electron backscatter diffraction (EBSD) technique. Results show that only dislocation slip is activated during RT rolling while both slip and twinning occur in LNT-rolled specimens. There are always some non-deforming grains after RT rolling because their orientations with the c-axes close to the normal direction (ND) of the Zr sheet are unfavorable for slip. The LNT rolling allows these non-deforming grains to be deformed by 11 2 ¯ 2 < 11 ¯ 23 > compressive twinning and thus leads to more homogenous microstructures. The angle between basal pole peaks and the ND slightly decreases during RT rolling, which is attributed to the activity of 10 1 ¯ 1 < 11 2 ¯ 3 > pyramidal slip. Many twins initiated at the early stage of LNT rolling could help retard the centralization of bimodal basal texture. In addition, calculations in light of key structural parameters measured by the EBSD reveal that the contribution from grain refinement induced by twinning makes the LNT-rolled specimens harder than the RT-rolled specimens. Graphical abstract: Highlights: Non-deforming grains are always present in pure Zr sheet rolled at room temperature. Both slip and twinning are activated during rolling at liquid nitrogen temperature, promoting more homogeneous microstructure. Twinning can make a significant contribution to the hardening of Zr sheet during rolling.